REGIONAL DEVELOPMENT AND SOCIOECONOMIC DIFFERENCES IN THE STATE OF MATO GROSSO DO SUL: THE PULP INDUSTRY AND OPTIONS FOR THE IVINHEMA VALLEY (REMUNOM, 2025)
The state of Mato Grosso do Sul has undergone significant economic transformations, driven by the growth of the pulp industry in regions such as Três Lagoas and Dourados. However, this progress is not evenly distributed, creating socioeconomic disparities between developed and less-developed areas, such as the Ivinhema Valley. This article analyzes the impacts of industrialization on reducing or worsening regional inequalities and proposes strategies for the sustainable development of the Ivinhema Valley, respecting current legislation and considering environmental and social aspects. The methodology includes secondary data analysis, case studies, and a literature review on regional economic development